Tamanho de gotas de pontas de pulverização em diferentes condições operacionais por meio da técnica de difração do raio laser - Bueno, Mariana R.; Cunha, João P. A. R. Da; Roman, Rodrigo A. A. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2013)
The present study aimed to evaluate the droplet spectrum of hydraulic nozzles, under different pressures and spray liquid compositions, using a laser particle size analyzer. In a completely randomized design, two air induction twin flat-fan nozzles (AD-IA/D 11002 and AD-IA/D11004) and two hollow-cone nozzles (MAG - 2 and MAG - 4) were evaluated, in factorial design 3 x 2: tree spray pressures (207, 276 and 345 kPa for twin flat-fan nozzles, and 414, 483 and 552 kPa for cone nozzles); and two spray liquid compositions (water and water plus phosphatydilcoline + propionic acid adjuvant). The addition of adjuvant reduced the volume median diameter for the AD-IA/D 11002 and 11004 nozzles; however it had an opposite effect with the MAG - 4 nozzles and not changed with the MAG - 2 nozzles. In adverse weather conditions, it is not recommended the use of hollow cone spray nozzle, even with the addition of adjuvant tested because of the high risk potential of drift.

O presente trabalho objetivou avaliar o espectro de gotas de pontas de pulverização hidráulicas, submetidas a diferentes pressões e composições de calda, por meio de um analisador de partículas a laser. Em delineamento inteiramente casualizado, avaliaram-se duas pontas de jato plano duplo com indução de ar (AD-IA/D 11002 e AD-IA/D 11004) e duas pontas de jato cônico vazio (MAG - 2 e MAG - 4), em esquema fatorial 3 x 2: três pressões de pulverização (207, 276 e 345 kPa para as pontas de jato plano duplo e 414; 483 e 552 kPa para as pontas de jato cônico); e duas composições de calda (água e água mais o adjuvante fosfatidilcoline + ácido propiônico). A adição do adjuvante reduziu o diâmetro da mediana volumétrica das gotas pulverizadas pelas pontas AD-IA/D 11002 e 11004; porém, teve efeito inverso com a ponta MAG - 4 e não o alterou com a ponta MAG - 2. Em condições climáticas adversas, não se recomenda o uso de pontas de jato cônico vazio, mesmo com a adição do adjuvante testado, em virtude do alto risco potencial de deriva.
Droplet size of spray nozzles in different operational conditions using laser difraction technique
Keywords: droplet size; spray technology; Surfactant; Espectro de gotas; Tecnologia de aplicação; Adjuvante